Passive ventricular remodeling in cardiac disease: focus on heterogeneity - Kessler, Elise L.; Boulaksil, Mohamed; van Rijen, Harold V. M.; Vos, Marc A.; van Veen, Toon A. B. (Frontiers in Physiology, 2014)
Passive ventricular remodeling is defined by the process of molecular ventricular adaptation to different forms of cardiac pathophysiology. It includes changes in tissue architecture, such as hypertrophy, fiber disarray, alterations in cell size and fibrosis. Besides that, it also includes molecular remodeling of gap junctions, especially those composed by Connexin43 proteins (Cx43) in the ventricles that affect cell-to-cell propagation of the electrical impulse, and changes in the sodium channels that modify excitability. All those alterations appear mainly in a heterogeneous manner, creating irregular and inhomogeneous electrical and mechanical coupling throughout the heart. This can predispose to reentry arrhythmias and adds to a further deterioration into heart failure. In this review, passive ventricular remodeling is described in Hypertrophic Cardiomyopathy (HCM), Dilated Cardiomyopathy (DCM), Ischemic Cardiomyopathy (ICM), and Arrhythmogenic Cardiomyopathy (ACM), with a main focus on the heterogeneity of those alterations mentioned above.